Investigating the Effects of Technology Integration, Performance Perception, and Ease of Understanding on Semantic Intention, and Performance Mediated by Behavioral Intention and Student and Teacher Satisfaction (Case Study: Nonprofit Elementary Schools) - Leila pirhaji Khozani; Sanaz Shafiee; javad Shekarriz (رویکردهای نوین آموزشی, 2021)
Today, e-learning has penetrated many levels of education and training, but the intention to continue in such a system is still at a very low level, and as a result, the future of the system is unpredictable. Given that e-learning is the main tool of competitive differentiation in schools, universities and educational centers, there is no guarantee of success without focusing on the intention of continuing the e-learning system. The aim of this study was to Investigating the Effects of Technology Integration, Performance Perception, and Ease of Understanding on Semantic Intention, and Performance Mediated by Behavioral Intention and Student and Teacher Satisfaction. The effect statistical population of this study was all students and teachers of non-profit primary schools in Khomeini Shahr. Cochran's formula was used to determine the sample size, in which 353 students and 151 teachers were selected. After collecting data through a questionnaire, the model was assessed with 7 components (technology integration, understanding of efficiency, understanding of ease of use, user satisfaction, intention to continue e-learning, behavioral intention and academic performance). In the analytical section, Smart PLS software was used to check the validity or quality of the model. Research findings show that understanding ease of use on understanding performance, integrating technology on behavioral intentions, understanding efficiency on behavioral intentions, understanding ease of use on behavioral intentions, understanding performance on student and teacher satisfaction, understanding ease of use on student and teacher satisfaction, intention Behavior affects academic performance, academic performance affects the intention to continue and on student and teacher satisfaction affects the intention to continue. The findings of this study can be used by school principals to promote students' academic achievement in all situations.